(untitled) (Research, Society and Development, 2022)
The present work aimed to verify the knowledge of public managers in the municipality of Palmeira das Missões, Rio Grande do Sul, about the importance of water resources in their area of ​​operation. To this end, a questionnaire with open and closed questions was applied to a total of 20 managers representing different institutions in the municipality. A qualitative-quantitative, cross-sectional and exploratory research was conducted. For that, data was collected through a questionnaire applied to 20 managers working in the public administration of that municipality. Numerical data analysis was performed using the quantitative statistical analysis method using the STATA software version 12.1 and considering the value of 5% as a reference for statistical significance (p-value<0.05). Qualitative data were understood, in close relationship with the first, through content analysis. The results showed that the vast majority of public managers do not have a deep knowledge of existing water resources, but recognize that they are being impacted and are degraded. Therefore, the municipality must propose actions aiming at a better performance of the servers responsible for the environmental area in the elaboration and execution of projects that aim at the preservation and recovery of the existing water resources. Such direction would help so that the problem of water resources can be faced by the active participation of public managers and the population through Environmental Education.